A Designed Conformational Shift To Control Protein Binding Specificity1. (12th August 2014) - Michielssens, Servaas; Peters, Jan Henning; Ban, David; Pratihar, Supriya; Seeliger, Daniel; Sharma, Monika; Giller, Karin; Sabo, Thomas Michael; Becker, Stefan; Lee, Donghan; Griesinger, Christian; de Groot, Bert L.
Abstract In a conformational selection scenario, manipulating the populations of binding‐competent states should be expected to affect protein binding. We demonstrate how in silico designed point mutations within the core of ubiquitin, remote from the binding interface, change the binding specificity by shifting the conformational equilibrium of the ground‐state ensemble between open and closed substates that have a similar population in the wild‐type protein. Binding affinities determined by NMR titration experiments agree with the predictions, thereby showing that, indeed, a shift in the conformational equilibrium enables us to alter ubiquitin's binding specificity and hence its function. Thus, we present a novel route towards designing specific binding by a conformational shift through exploiting the fact that conformational selection depends on the concentration of binding‐competent substates.